Theoretical Cognition and Practical Design of a High-Quality Teacher Education System for Building a Country Strongin Education: An Interview with Professor Liu Haimin from Northeast Normal University - LIU Haimin; MAN Ying (Jiaoshi jiaoyu xuebao)
Professor Liu Haimin has long been committed to academic research on education quality and education system development. Following the introduction of the discourse on high-quality development in the field of economy, Professor Liu led his team to pioneer research on high-quality education development, and was successively approved fortwo major projects funded by the National Social Science Fund of China, namely"Research on the Paths and Countermeasures for the High-Quality Development of Chinese Education in the New Era"and "Research on the Connotation, Comparison, and Construction Paths of a High-Quality Education System". In recent years, he has produced a series of academic achievements centered around "high-quality education development". A high-quality teacher force is the key support for high-quality education development and the backbone of building a strong country in education. Professor Liu elaborated on the theoretical and practical design of a high-quality teacher education system in supporting the construction of a strong country in education. The value of a high-quality teacher education system for the construction is reflected both in its support for the construction of a high-quality education system and in addressing the practical needs of overcoming disciplines development dilemmas. The connotative features of a high-quality teacher education system should firmly hold three key points: "high quality", "systematization", and "autonomy". Currently, teacher education has supported China in establishing the world's largest education system, and continuous innovation in teacher education models has effectively promoted the overall improvement of teachers'qualities. The high-quality teacher education system is continuously enhancing China's international competitiveness in education. In the context of building a strong country in education, the construction of a high-quality teacher education system requires the guidance of an educationalist spirit, scientific and systematic institution design, as well as efficient and flexible education governance.